Expression System Based on an MTIIa Promoter to Produce hPSA in Mammalian Cell Cultures - Santos, Anderson K.; Parreira, Ricardo C.; Resende, Rodrigo R. (Frontiers in Microbiology, 2016)
Because of the limitations of standard culture techniques, the development of new recombinant protein expression systems with biotechnological potential is a key challenge. Ideally, such systems should be able to effectively and accurately synthesize a protein of interest with intrinsic metabolic capacity. Here, we describe such a system that was designed based on a plasmid vector containing promoter elements derived from the metallothionein MTIIa promoter, as well as processing and purification elements. This promoter can be induced by heavy metals in a culture medium to induce the synthesis of human prostate-specific antigen (hPSA), which has been modified to insert elements for purification, proteolysis, and secretion. We optimized hPSA production in this system by comparing the effects and contributions of ZnCl2, CdCl2, and CuSO4 in HEK293FT, HeLa, BHK-21, and CHO-K1 cells. We also compared the effectiveness of three different transfection agents: multi-walled carbon nanotubes, Lipofectamine 2000, and X-tremeGENE HP Reagent. hPSA production was confirmed via the detection of enhanced green fluorescent protein fluorescence, and cell viability was determined. The expression of hPSA was compared with that of the native protein produced by LNCaP cells, using enzyme-linked immunosorbent assay and sodium dodecyl sulphate polyacrylamide gel electrophoresis. X-tremeGENE reagent, the BHK-21 cell line, and CuSO4 showed the highest hPSA production rates. Furthermore, BHK-21 cells were more resistant to the oxidative stress caused by 100 μM CuSO4. These results suggest that the proposed optimized inducible expression system can effectively produce recombinant proteins with desired characteristics for a wide range of applications in molecular biology.